Debating Divorce : Moral Conflict in Ireland - Dillon, Michele, 1960- (Book collections on Project MUSE., 1993)
In 1986 a national opinion poll indicated that over half of Irish voters favored an upcoming referendum to remove the constitutional ban on divorce. Yet, after nine weeks of vigorous debate during which forces on both sides of the issue presented their cases to the public, the amendment was defeated. In Debating Divorce, Michele Dillon uses the divorce referendum debate in Ireland as a base from which to explore the long-standing sociological preoccupation with how societies decide questions of values. Focusing on culture and moral conflict, she examines the stances adopted by the major player.